Investigating Problems and Difficulties of Speaking That Encounter English Language Speaking Students of Junior High School - Candraloka, Olyvia Revalita; Rosdiana, Aliva ((JELE) Journal Of English Language and Education, 2019)
This study is aimed at investigating the students’ ability, the problems of why they faced problems on English speaking. The triangulation of mixed methods was used in this study to show and measure the speaking difficulties encountered by students of 7th grade Junior High School at MTS N 2 Kudus. The quantitative data gathered from the speaking test result in by involving 31 students of MTSN 2 Kudus and the qualitative data gathered from the questionnaire and interview results from the selected students who meet criteria. The findings showed that the students’ ability was categorized difficulties in speaking English (26.009); the students have problems on vocabulary (100%), pronunciation (100%), grammar (83.9%), and fluency (96.7%).  The causes of problems faced by students on English speaking that English were not only having limited knowledge on the components of speaking skills including vocabulary, pronunciation, grammar, and fluency but also they have their own personal reasons, such shyness, anxiety, confusion, lack confidence, and fear of making mistake. This study indicated that the students’ ability should be increased by giving motivation and taught them with th esuitable and interested English speaking materials.